Preparation of Activated Carbon from Various Biomasses by Single-Stage Pyrolysis - Suwimon Thowphan; Napat Kaewtrakulchai; Anuchit Jaruvanawat; Sutee Chutipaijit; Pramote Puengjinda; Nuwong Chollacoop; Masayoshi Fuji; Apiluck Eiad‐ua (Journal of Physics Conference Series, 2022)
Abstract Nowadays, activated carbon were successfully synthesized from biomass, Activated nanoporous carbon have been widely for several applications such as solution to air pollution, solution to water pollution. In this work, study the effects of pyrolysis temperature of activated carbon synthesized from coconut shell, coconut leaves, coconut bracts, cattail flower, cattail leaves, mangosteen bracts, durian bracts, corn leaves, eucalyptus bracts, sugarcane leaves and toddy palm bracts. The pyrolysis of various biomass was studied at the temperature of 700-900 °C for 2 h under N2 flow of 100 ml/min. The results showed that biomass types and pyrolysis temperature affects the structural and physicochemical properties of activated carbon such as pore structures, surface functional groups and elemental compositions. activated carbon obtained at 800 °C for 2 h had the highest composed of amorphous phase, porosity and surface area.
Keywords: Adsorption and biosorption for pollutant removal; Thermochemical Biomass Conversion Processes; Natural Products and Applications